US-China Cooperation on Climate Change at COP26: Policy Implications for Environment and Energy - 이왕휘 (Journal of Safety and Crisis Management, 2022)
Despite fierce strategic competition, the United States and China reached to a breakthrough agreement at COP26. This article addresses how and why the two superpowers chose to cooperate on environment and energy. Scientific evidence of global warming pressured the largest and second-largest carbon emitters to bear the responsibility and burden of climate change. In addition, there has been a growing interdependence between them since the Obama administration. As the US became an oil and gas exporting country in the late 2010, the Trump administration pushed ahead with selling oil and gas surpluses to China that rapidly increased energy imports. In pursuit of a Global Green New Deal, the Biden administration made efforts to help China achieve carbon neutrality as early as possible. For China, natural gas can be a second-best option during energy transition because it emits less carbon than coal. US gas also contributes to diversifying energy imports. These mutual interests played a crucial role in insulating climate change cooperation from strategic competition.
Keywords: United States; China; climate change; energy; COP26